Increased Sociability in Mice Lacking Intergenic Dlx Enhancers - Fazel Darbandi, Siavash; Esau, Crystal; Lesage-Pelletier, Cindy; Monis, Simon; Poitras, Luc; Yu, Man; Perin, Sofia; Hatch, Gary; Ekker, Marc (Frontiers in Neuroscience, 2021)
The Dlx homeodomain transcription factors play important roles in the differentiation and migration of GABAergic interneuron precursors. The mouse and human genomes each have six Dlx genes organized into three convergently transcribed bigene clusters (Dlx1/2, Dlx3/4 and Dlx5/6) with cis-regulatory elements (CREs) located in the intergenic region of each cluster. Amongst these, the I56i and I12b enhancers from the Dlx1/2 and Dlx5/6 locus, respectively, are active in the developing forebrain. I56i is also a binding site for GTF2I, a transcription factor whose function is associated with increased sociability and Williams-Beuren syndrome. In determining the regulatory roles of these CREs on forebrain development, we have generated mutant mouse-lines where Dlx forebrain intergenic enhancers have been deleted (I56i(-/-), I12b(-/-)) or have been mutated with a single nucleotide polymorphism associated with cases of autism (vI56i). Loss of Dlx intergenic enhancers impairs expression of Dlx genes as well as some of their downstream targets or associated genes including Gad2 and Evf2. The loss of the I56i enhancer resulted in a transient decrease in GABA+ cells in the developing forebrain. The intergenic enhancer mutants also demonstrate increased sociability and learning deficits in a fear conditioning test. Characterizing mice with mutated Dlx intergenic enhancers will help us to further enhance our understanding of the role of these Dlx genes in forebrain development.